Gender Justice and Family Welfare in Qur’anic Perspectives on Interfaith Marriage and Polygamy: A Thematic Study - Helga Juliya; Rizki Rahmadani; Safa Anzila Madaniah (Mir'ah: Family Law and Legal Culture, 2026)
This study examines Qur'anic perspectives on interfaith marriage and polygamy through a thematic (maudhu'i) interpretation approach and analyzes their implications for gender justice and family welfare in Islamic law. Using qualitative descriptive library research, this study examines Qur'anic verses, hadith, classical and contemporary tafsir literature, and relevant scholarly references. The findings reveal that the Qur'an prohibits marriages between Muslim women and non-Muslim men and forbids marriage with polytheists to safeguard faith, family harmony, and religious upbringing of future generations. Polygamy is permitted as a conditional concession limited to four wives, provided justice can be maintained; however, the Qur'an acknowledges the difficulty of achieving perfect justice, implying monogamy is preferable when fairness cannot be guaranteed. These regulations significantly impact marriage validity, inheritance rights, religious practices within the family, and spousal social-economic responsibilities. This research contributes to contemporary thematic exegesis by presenting a balanced, textually-grounded yet contextually-sensitive analysis responsive to modern challenges, particularly addressing gender justice and family welfare holistically. However, limitations include exclusive reliance on library research without field data, limited scope to two themes without exploring other contemporary family law issues, and dominance of Sunni perspectives without adequate discussion of minority or alternative interpretations. Overall, Qur'anic regulations concerning interfaith marriage and polygamy demonstrate a strong commitment to protecting religious faith, promoting gender justice, preserving family welfare, and realizing Islamic family law objectives in contemporary society.